Clinical manifestations and oral findings in fraser syndrome - Diniz, Michele Baffi [UNESP]; Lima, Luciana Monti [UNESP]; Sacono, Nancy Tomoko [UNESP]; De Paula, Andréia Bolzan; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (My University, 2007)
This article is the first known case report of Fraser syndrome in the dental literature. Its purpose was to present the clinical manifestations, oral findings, and dental treatment of a 14-year, 10-month-old female patient. Fraser syndrome is a rare recessive autosomal genetic disorder characterized by multisystemic malformation, usually comprising cryptophthalmos, syndactyly, and renal defects. The child presented with: (1) hydrocephaly; (2) face asymmetry; (3) low-inserted ears; (4) flat nose bridge; (5) cryptophthalmos; (6) bilateral absence of eyeballs; (7) hypertelorism; (8) syndactyly on the left fingers and toes; (9) skeletal defects; and (10) lower limb asymmetry. The intraoral examination revealed: (1) complete primary denture; (2) malocclusion; (3) tooth crowding; (4) ogival palate; (5) normal labial frena; (6) absence of lingual frenum (not compromising the tongue movements); (7) parched lips; (8) supragingival calculus adhered to all tooth surfaces; and (9) moderate gingivitis. The dental treatment consisted of periodic monitoring of the patient's oral health status and supragingival scaling associated with topical applications of 0.12% chlorhexidine digluconate gel at 2-week intervals to reduce gingivitis.
Keywords: Fraser syndrome; Oral findings; Tooth anomalies; congenital malformation; consanguinity; dentition; eye malformation; female; gingivitis; hard palate; human; hypertelorism; malocclusion; mouth disease; multiple malformation syndrome; pathology; preschool child; preventive dentistry; syndactyly; syndrome; tongue; tooth calculus; Abnormalities, Multiple; Child, Preschool; Consanguinity; Dental Calculus; Dental Scaling; Dentition, Primary; Eye Abnormalities; Female; Gingivitis; Humans; Hypertelorism; Lingual Frenum; Malocclusion; Mouth Abnormalities; Palate, Hard; Syndactyly; Syndrome